2009
DOI: 10.1038/ki.2008.697
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus reduces nitric oxide synthase function by binding to FKBP rather than by its calcineurin effect

Abstract: Hypertension develops in many patients receiving the immunosuppressive drug tacrolimus (FK506). One possible mechanism for hypertension is a reduction in vasodilatory nitric oxide. We found that tacrolimus and a calcineurin autoinhibitory peptide significantly decreased vascular calcineurin activity; however, only tacrolimus altered intracellular calcium release in mouse aortic endothelial cells. In mouse aortas, incubation with tacrolimus increased protein kinase C activity and basal endothelial nitric oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 33 publications
3
63
1
Order By: Relevance
“…The observation in the SD rats is consistent with previous reports (43) and is likely a result of effects of this agent to decrease nitric oxide production by calcineurin-independent effects (9). In contrast to the prohypertensive effects in normal rats, however, administration of tacrolimus to the Dahl SS rat decreased infiltration of T cells in the kidney, decreased renal oxidative stress, and attenuated sodium-dependent hypertension and renal disease in these rats.…”
Section: Discussionsupporting
confidence: 81%
“…The observation in the SD rats is consistent with previous reports (43) and is likely a result of effects of this agent to decrease nitric oxide production by calcineurin-independent effects (9). In contrast to the prohypertensive effects in normal rats, however, administration of tacrolimus to the Dahl SS rat decreased infiltration of T cells in the kidney, decreased renal oxidative stress, and attenuated sodium-dependent hypertension and renal disease in these rats.…”
Section: Discussionsupporting
confidence: 81%
“…However, we found that the acute effects of FK506 on eNOS were completely independent of calcineurin inhibition (Cook et al, 2009). Thus, it still remains to be elucidated which of the four cPKC isoforms (␣, ␤ I, ␤ II , and ␥) is responsible for the phosphorylation of eNOS at Thr495 in response to FK506.…”
Section: Introductionmentioning
confidence: 74%
“…Phosphorylation of Ser1177, Ser633, and Tyr83 stimulates eNOS activity, whereas phosphorylation at Thr495 and Ser116 inhibits eNOS activity (Mount et al, 2007;Fulton et al, 2008). We found that FK506, via inhibition of its intracellular target FK506 binding protein 12 (FKBP12), causes a concentrationdependent increase in eNOS Thr495 phosphorylation, decreases vasodilation, and increases blood pressure (Long et al, 2007;Cook et al, 2009). This is caused by the displacement of FKBP12 from intracellular calcium channels (ryanodine receptors), leading to an intracellular Ca 2ϩ leak that activates the conventional protein kinase C (cPKC) isoforms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations